Redescriptions of Polysteganus coeruleopunctatus (Klunzinger 1870) and P. lineopunctatus (Boulenger 1903), with two new species from Western Indian Ocean - Iwatsuki, Yukio; Heemstra, Phillip C. (Zootaxa, 2015)
Five valid species in the genus Polysteganus (Pisces; Sparidae) from the Western Indian Ocean are currently known: P. baissaci Smith 1978, P. coeruleopunctatus (Klunzinger 1870), P. mascarenensis Iwatsuki & Heemstra, 2011, P. praeorbitalis (Günther 1859), and P. undulosus (Regan 1908). Although P. lineopunctatus (Boulenger 1903) has long been synonymized under P. coeruleopunctatus, both species are redescribed as valid. Two new species of Polysteganus were discovered in the course of this review. Polysteganus flavodorsalis n. sp. is described on the basis of six type specimens (143–265 mm SL) from Nazareth Bank, Mascarene Plateau, Indian Ocean, and P. cerasinus n. sp. is described based on the holotype (134 mm SL) from Saya de Malha Bank. Provisional distribution patterns of the eight valid species of Polysteganus in the Western Indian Ocean are discussed. A key to the species of Polysteganus is provided.